2010
DOI: 10.1002/adsc.201000085
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopalladated Ferrocenylimine as Efficient Catalyst for the Syntheses of Arylboronate Esters

Abstract: The cyclopalladated ferrocenylimine I and its phosphine adducts IIa-f were prepared and evaluated in the borylation of aryl halides. The tricyclohexylphosphine adduct IIb exhibited highly catalytic activity for the coupling of aryl and heteroaryl bromides containing various functional groups with low catalyst loading (2 mol%). Aryl and heteroaryl chlorides were smoothly converted into the corresponding boronates in the presence of the monophosphinobiaryl ligand (XPhos) adduct IIf. It was proposed that palladac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Through a thorough literature search of heteroaryl boronates synthesized from B 2 Pin 2 or H-BPin, two trends can be found: either the method reported is purely for one functionalized heteroaryl, 5060 or only a few examples were synthesized under reaction conditions considered under a “general” methods procedure. 14,40,42,44,6164 Also noteworthy is that the heteroaryls examined in this search are among just a handful of heteroaryl borylated products that can be found in the literature, and there is no publication dedicated solely to the Miyaura borylation of heteroaryls using B 2 Pin 2 . Our findings, coupled with the literature results, provide evidence that a general method for the borylation of hetereoaryls remains elusive, and that each substrate or general class of substrates may need to be treated on a case-by-case basis.…”
Section: Resultsmentioning
confidence: 99%
“…Through a thorough literature search of heteroaryl boronates synthesized from B 2 Pin 2 or H-BPin, two trends can be found: either the method reported is purely for one functionalized heteroaryl, 5060 or only a few examples were synthesized under reaction conditions considered under a “general” methods procedure. 14,40,42,44,6164 Also noteworthy is that the heteroaryls examined in this search are among just a handful of heteroaryl borylated products that can be found in the literature, and there is no publication dedicated solely to the Miyaura borylation of heteroaryls using B 2 Pin 2 . Our findings, coupled with the literature results, provide evidence that a general method for the borylation of hetereoaryls remains elusive, and that each substrate or general class of substrates may need to be treated on a case-by-case basis.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the active species was proposed to be a Pd(0) ''Pd-PR 3 '' species, and it was shown that the cyclopalladated ligand was released from the metal center during activation [27,28]. We have also found that these monophosphine-palladacycles are far more active than the corresponding dimeric palladacycles.…”
Section: Application In Suzuki Coupling Reactionsmentioning
confidence: 94%
“…The most commonly used tetraalkoxydiboron was bis(pinacolato)diboron (B 2 Pin 2 , 9). [54][55][56][57][58][59][60][61][62] Other tetraalkoxydiboron compounds such as (neopentylglycolato)diboron (10) were also reported. 63 Dialkoxyhydroborane compounds like (pinacolato)-hydroborane (HBPin, 11) are occasionally reported as well.…”
Section: Synthesis Of Pyridinylboronic Acids and Esters By Palladium-mentioning
confidence: 99%
“…13, where L = 12). 57 KOAc is generally used as the base, as stronger bases (e.g. K 3 PO 4 and K 2 CO 3 ) may lead to side reactions such as homo-coupling.…”
Section: Synthesis Of Pyridinylboronic Acids and Esters By Palladium-mentioning
confidence: 99%
See 1 more Smart Citation